The Strategy Of The Merauke Regency Government In Managing Wamanggu Market - Hubertus B M Letsoin; Fitriani; Nur Jalal (PAPSEL Research and Consulting, 2026)
This study aims to analyse the strategy of the Merauke Regency Government in managing Wamanggu Market and to identify the factors influencing its implementation. The research employed a qualitative descriptive approach, with data collected through interviews, observations, and documentation. The informants included the Head of the Department of Industry, Trade, Cooperatives and Small and Medium Enterprises (SMEs) of Merauke Regency, the Head of the Trade Division, the Head of the Wamanggu Market Technical Implementation Unit (UPTD), the Chairperson of HIPPAM, market traders, and consumers. Data were analysed using data reduction, data presentation, and conclusion drawing techniques. The findings indicate that the management strategy of Wamanggu Market is implemented through four main aspects: trader registration, trader regulation and enforcement, market management evaluation, and the enforcement of trader discipline. However, the implementation of these strategies has not yet been fully effective. Trader registration continues to rely on outdated data, resulting in discrepancies between administrative records and actual field conditions. Regulatory measures have not been entirely successful, as some traders continue to operate outside the designated market area and kiosk allocation does not always comply with established zoning arrangements. Market management evaluations are conducted regularly; however, follow-up actions have not been sufficient to resolve existing problems significantly. Furthermore, the enforcement of trader discipline remains constrained by low levels of compliance among traders and the inconsistent application of regulations.The study also reveals that market management strategies are influenced by internal factors, including limitations in human resources, infrastructure, budget availability, and inter-agency coordination, as well as external factors such as regulatory frameworks, trader participation, environmental conditions, market dynamics, and consumer behaviour. Therefore, improvements in human resource capacity, stronger institutional coordination, enhanced infrastructure, and the development of adaptive management strategies are necessary to achieve more effective and sustainable management of Wamanggu Market.